2022
DOI: 10.1155/2022/3716849
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Sandplay Therapy on the Mental Health Level of College Students

Abstract: To analyze the effect of sandplay (SP) therapy on the mental health level of college students. 500 college students were openly recruited, using the University Student Mental Health Questionnaire (UPI) to screen out 76 students in the UPI category. 34 college students were randomly selected and divided into two groups, 17 in the control group and 17 in the SP therapy group (experimental group); the control group received no treatment, and the experimental group was treated with SP therapy, to analyze the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%